Ādhyātmikatā aura Harayāṇavī saṃskrtibodha : Svāmī Ātmānanda jī kī racanāoṃ ke viśesha sandarbha meṃ - Bhāradvāja, Rāma Kumāra, 1946- (Cintā Prakāśana, 1981)
Study on Haryana's culture and spiritualism as reflected in the works of Swami Ātmānanda, Hindu religious leader from Haryana.